2021
DOI: 10.1186/s12939-021-01405-6
|View full text |Cite
|
Sign up to set email alerts
|

Disparity in physician-patient communication by ethnicity: evidence from Bangladesh

Abstract: Background Physician-patient communication behavior (PPCB) is the primary process by which medical decision-making occurs and health outcome depends. Physician-patient communication differences may partly from the ethnic disparities. To examine this problem, this study aims to explore whether physician-patient communication differs by ethnicity during primary care medical consultations. Methods The study was conducted among the Bengali and ethnic m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Patients, on the other hand, are more likely to get involved in expressing their concerns, asking questions and giving opinions about their treatment in a consultation in which the doctor provides supportive communication behaviors. Our results, consistently with previous studies, showed a correlation between appointment duration and doctors’ patient-centered behavior [ 2 , 3 , 4 , 10 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Patients, on the other hand, are more likely to get involved in expressing their concerns, asking questions and giving opinions about their treatment in a consultation in which the doctor provides supportive communication behaviors. Our results, consistently with previous studies, showed a correlation between appointment duration and doctors’ patient-centered behavior [ 2 , 3 , 4 , 10 , 25 , 26 , 27 , 28 , 29 , 30 ].…”
Section: Discussionsupporting
confidence: 93%
“…Different studies show that affectionate behavior from physicians stimulates patients' participation in treatment. 11 In this study, there were three patients (3, 7.5%) who underwent social harassment and became isolated after 1 st diagnosis of cancer. Social molestation might arise from different social stigmas.…”
Section: Discussionmentioning
confidence: 72%
“…Effective physician-patient communication serves as a motivator, incentive, assurance source, and encouragement for the patient [ 14 , 15 , 16 ]. Additionally, effective physician-patient communication can assist patients in managing their emotions, facilitating the interpretation of medical information, and allowing for a more accurate assessment of their needs, perceptions, and expectations [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%